(untitled) (World Science, 2019)
Ankylosing spondylitis is a chronic systemic disease of the connective tissue which affects primarily joints and ligaments of the spine, peripheral joints and internal organs, causing progressive development of limited spinal mobility due to ankylosing of epiphyseal joints, formation of syndesmosis and calcification of vertebral ligaments. There are currently no methods that can completely cure or stop the progression of ankylosing spondylitis, however, manual therapy combined with shock- wave therapy is able to quickly, non-invasively, effectively, economically, safely and without side effects support patients, improving their quality of life, prolonging the duration of the remissions, reducing the frequency of relapses, significantly delaying the development of structural damage and the progression of bone ankylosis. This study discusses the effect of manual therapy combined with shock wave therapy on ankylosing spondylitis resistant to other treatments.